Effects of Neurotrophic Support and Amyloid-Targeted Combined Therapy on Adult Hippocampal Neurogenesis in a Transgenic Model of Alzheimer's Disease - Morrone, Christopher D.; Thomason, Lynsie A. M.; Brown, Mary E.; Aubert, Isabelle; McLaurin, JoAnne (PLOS ONE, 2016)
Although it is recognized that multi-drug therapies may be necessary to combat AD, there is a paucity of preclinical proof of concept studies. We present a combination treatment paradigm, which temporally affects different aspects of Alzheimer’s disease (AD)-like pathology, specifically Aβ-toxicity and neurogenesis. At early stages of AD-like pathology, in TgCRND8 mice, we found that combating Aβ pathology with scyllo-inositol ameliorated deficits in neurogenesis. Older TgCRND8 mice with established amyloid load had decreased progenitor cell proliferation and survival compared to non-transgenic mice, regardless of scyllo-inositol treatment. The prolonged exposure to Aβ-pathology leads to deficits in the neurogenic niche, thus targeting Aβ alone is insufficient to rescue neurogenesis. To support the neurogenic niche, we combined scyllo-inositol treatment with leteprinim potassium (neotrofin), the latter of which stimulates neurotrophin expression. We show that the combination treatment of scyllo-inositol and neotrofin enhances neuronal survival and differentiation. We propose this proof of concept combination therapy of targeting Aβ-pathology and neurotrophin deficits as a potential treatment for AD.